The Benefits and Challenges of Managing Asthma in Hispanic Families in South Texas: A Mixed-Methods Study - Carrillo, Genny; Perez-Patron, Maria J.; Lucio, Rose L.; Cabrera, Lucia; Trevino, Alyssa; Xu, Xiaohui; Mier, Nelda (Frontiers in Public Health, 2017)
Background: Understanding the experience of Hispanic parents of children diagnosed with asthma can be useful in the delivery of effective and meaningful asthma education. In order to assess the needs of Hispanic families with asthmatic children in South Texas, investigators utilized a combination of qualitative and quantitative research methods. Objectives: This study aimed 1) to assess the impact of asthma in the quality of life of Hispanic children and their families; and 2) to identify barriers and challenges to asthma management as perceived by parents of children diagnosed with asthma. Methods: A mixed-methods study including a quality of life survey and focus group discussions. The Children’s Health Survey of Asthma (CHSA) was completed by 90 parents of children with asthma. Three focus groups were conducted with 15 low-income, Hispanic parents of asthmatic children to assess their needs and experience managing the disease. Results: Results from the CHSA showed that asthma significantly affects the quality of life of children with asthma and their families, particularly the emotional dimensions and the child’s physical health. Fifty-three percent of the children had visited the emergency room and 51% had been hospitalized due to asthma. One out of five parents had missed work and 27% of children had missed school in the past two weeks due to the child’s asthma. In the focus group discussions, the key themes emerging included lack of asthma knowledge, the burden of disease for asthmatic children and their families, and the importance of asthma education and self-management behaviors for asthma control. Conclusions: One of the main challenges faced by Hispanic families with asthmatic children is the lack of asthma-related knowledge to help understand and control their children’s disease. Lack of knowledge and self-management skills lead to significant stress and anxiety among children with asthma and their parents. Results highlight that while asthma has an effect on the quality of life of children and their families, particularly on the emotional health domain, a wide dissemination of asthma management education in different settings might help prevent asthma attacks and improve symptom control among those suffering from this disease along the US-Mexico border.